A new viral ringspot disease of citrus (Citrus species) in India - Byadgi, A S; Ahlawat, Y S (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during 1990–1993 to study ringspot disease of citrus (Citrusspp), its distribution, host range, etiological agent and economic importance. A diseasewith ringspot symptoms was found widely distributed in most commercial citrus cultivars,viz. ’Malta’, ’Mosambi’ and ’Satgudi’ of sweet orange [Citrus sinensis (L.) Pers.] ’NagpurOrange’ and ’Kinnow Mandarin’ of mandarin (C. reticulata Blanco); and ’Kagzi Lime’ and’Kagzi Kalan’ of lime [C. auran tifolia (Christen.) Swingle]. The disease was foundtransmitted by grafting and dodder (Cuscula reflexa Roxb.) from citrus to citrus but not bysap, seed, soil and 4 aphid species, viz cotton aphid (Aphis gossypii Glover), green citrusaphid (A. citricola van der Goot), groundnut aphid (A. craccivora Koch) and green peachaphid [Myzus persicae (Sluz.)]. Three types of filamentous particles of 640 nm X 15 nm, 690nm X 9 nm and 2 250 nm x 40 nm were found associated with the disease in purified as well asin leaf-dip preparations. Particles of 2250 nm x 40 nm were in the form of tubules and wererecorded for the first time with viral infection in citrus and helped in diagnosis of thedisease. Host range, virion morphology and presence of tubules indicated that thecitrus-ringspot disease in India is different from the ringspot and psorosis diseasesreported earlier from other parts of the world. In ’Kinnow Mandarin’ the disease caused20.54-98.38% loss in yield.